Measurement and data analysis for engineering and science - Dunn, Patrick F. (CRC Press/Taylor & Francis, 2010)
"Presenting the fundamental tools of experimentation that are currently used by engineers and scientists, Measurement and Data Analysis for Engineering and Science, Second Edition covers the basics of experimentation, hardware of experiments, and methods of data analysis. It also offers historical perspectives throughout." "Updating and reorganizing its popular predecessor, this second edition makes the text much easier to follow and enhances the presentation with electronic material. This edition includes more than 150 new problems, bringing the total to over 420 problems. It also offers a supplementary website that provides unit conversions, learning objectives, review crossword puzzles and solutions, differential equation derivations, laboratory exercise descriptions, MATLAB sidebars with M-files, and homework data files." "Thorough and up to date, this edition continues to help readers gain a fundamental understanding of the tools of experimentation. It discusses basic concepts related to experiments, measurement system components and responses, data analysis, and effective communication of experimental findings."--BOOK JACKET.